2022
DOI: 10.3390/healthcare10030583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Optimized Diet as an Adjunct to Non-Surgical Periodontal Therapy in Subjects with Periodontitis: A Prospective Study

Abstract: Diet and nutrition are generally categorized as modifiable lifestyle risk factors for the development of periodontal disease because diet may influence a person’s inflammatory status. This study aimed to evaluate the efficacy of the application of a diet plan focused on reducing inflammation and oxidative stress in treating periodontitis. Subjects suffering from periodontitis were divided into two groups. Both groups underwent non-surgical periodontal therapy, and in the optimized diet (OD) group, this treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…And in a prospective study, the diet of patients undergoing non-surgical periodontal treatment was optimized for 4 weeks (intake of vitamins, fiber, and restriction of TFA intake). This study found that the reduction of full-mouth bleeding score and PPD was more significant in the population with optimized diet than in the group with only periodontal treatment ( 29 ). In a cross-sectional study of patients with stable coronary artery disease ( 50 ), it was found that dietary patterns of patients with periodontitis favor the eating of fried foods, which are known to be rich in TFA.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…And in a prospective study, the diet of patients undergoing non-surgical periodontal treatment was optimized for 4 weeks (intake of vitamins, fiber, and restriction of TFA intake). This study found that the reduction of full-mouth bleeding score and PPD was more significant in the population with optimized diet than in the group with only periodontal treatment ( 29 ). In a cross-sectional study of patients with stable coronary artery disease ( 50 ), it was found that dietary patterns of patients with periodontitis favor the eating of fried foods, which are known to be rich in TFA.…”
Section: Discussionmentioning
confidence: 83%
“…Meanwhile, recent studies have found that EA consumption in the diet has a negative impact on the oral condition of mice, associated with periodontal bleeding ( 28 ). And for patients after periodontal treatment, banning EA-rich food intake can improve the periodontal prognosis ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…These in turn will lead to a deprivation of local oxygen in the area, favoring the development of anaerobic bacteria present in the gum cracks that in turn feed dysbiosis 55 and a sustained inflammatory reaction with further tissue damage, the so-called “ inflammatory dysbiotic cycle ” (IDC) ( Figure 5 ). A recent study 88 evaluated the efficacy of a low-carbohydrate diet plan characterized by a particular attention to the daily intake of whole-grain products and fiber, omega-3 fatty acids, sources of vitamin C, vitamin D, and antioxidants in reducing inflammation and oxidative stress in treating periodontitis. The authors found that the application of this optimized diet was associated with a higher reduction in probing pocket depth (PPD) and full-mouth bleeding score (FMBS) after the treatment.…”
Section: Main Oral Conditions Affected By Oral Microbiota “Imbalance”mentioning
confidence: 99%
“…The authors found that the application of this optimized diet was associated with a higher reduction in probing pocket depth (PPD) and full-mouth bleeding score (FMBS) after the treatment. 88 …”
Section: Main Oral Conditions Affected By Oral Microbiota “Imbalance”mentioning
confidence: 99%
“…Therapeutic interventions aiming to modulate the inflammation profile should include behavioral interventions, such as smoking and dietary consumption of calcium and vitamin D and the treatment of medical conditions (e.g., poorly controlled diabetes, stress, and osteopenia). Recently, obesity and low levels of physical activity were also classified as risk factors for periodontitis [ 18 ]. Among the innovative approaches for treating inflammatory conditions is also Hyperbaric oxygen (HBO) therapy which has been recently introduced and investigated for this clinical scenario with promising results [ 19 ].…”
Section: Introductionmentioning
confidence: 99%